Measuring Punishment and Reward Sensitivity in children and adolescents with a parent-report version of the Bis/Bas-scales. (December 2015) - Vervoort, L.; Vandeweghe, L.; Vandewalle, J.; Van Durme, K.; Vandevivere, E.; Wante, L.; McIntosh, K.; Verbeken, S.; Moens, E.; Goossens, L.; Braet, C.
Abstract: The present study examined the validity and reliability of the parent-report version of Carver and White's BIS/BAS-scales for children, measuring Punishment and Reward Sensitivity (PS and RS). Gender and age differences in PS and RS were explored. Mothers (n = 546, 62% girls, 2–18 years) completed the BIS/BAS parent-version and other instruments assessing PS/RS, personality and psychopathology. Reliability of most (sub-)scales was at least acceptable. The BIS/BAS-scales had meaningful relationships with other instruments assessing PS/RS, personality and psychopathology. There were significant age differences on BIS/BAS-scores, but no significant gender differences. The BIS/BAS parent-version is a valid and reliable parent-report PS/RS instrument for children and adolescents. Highlights: Punishment Sensitivity and Reward Sensitivity can be measured with parent report. The BIS/BAS parent version is reliable and valid. There are age differences in parent-reported PS and RS, but no gender differences.